Mango sales soar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
World mango production has doubled in the last twenty years. In 1997, 22 million tonnes were produced, 10 million in India alone. In Europe, it is now the fourth tropical fruit imported after pineapple, avocado and banana, with half the region's...